Analysis of Employee Competence and Public Services on Organizational Performance at the Tarogong Kaler District Office, Garut Regency - Yusana, Acep; Mulyaningsih; Ulumudin, Aceng; Yudiardi, Dodi; Triana H.S., Yagus (GoAcademica Research & Publishing, 2025)
This research is motivated by suboptimal organizational performance at the Tarogong Kaler District Office, Garut Regency, during the 2023–2024 period, particularly regarding the influence of employee competency and public service on organizational performance. The study aims to examine and analyze the effects of employee competency and public service on organizational performance. A quantitative research method was used, employing a descriptive approach and survey techniques, with a sample of 37 respondents. The main hypothesis testing shows that both employee competency and public service significantly influence organizational performance. Furthermore, employee competency has a significant impact on organizational performance, as does public service. The coefficient of determination also indicates that competency and service simultaneously affect organizational performance, although other unexamined variables also contribute. The findings reveal several key issues: in the competency variable, the procedural element remains suboptimal, while in the public service variable, the clarity of service delivery by employees needs improvement. Regarding organizational performance, the aspect of employee responsibility requires enhancement. Based on these findings, the study suggests that employee capabilities particularly in procedural execution should be improved through training and career development. The clarity of service delivery should be enhanced through regular evaluations, and employee responsibility should be strengthened through systemic improvements and organizational reforms.